2016
DOI: 10.1186/s12978-016-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

Labor and birth care by nurse with midwifery skills in Brazil

Abstract: BackgroundThe participation of nurses and midwives in vaginal birth care is limited in Brazil, and there are no national data regarding their involvement. The goal was to describe the participation of nurses and nurse-midwives in childbirth care in Brazil in the years 2011 and 2012, and to analyze the association between hospitals with nurses and nurse-midwives in labor and birth care and the use of good practices, and their influence in the reduction of unnecessary interventions, including cesarean sections.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
21

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 30 publications
5
52
0
21
Order By: Relevance
“…Regarding the freedom of movement and position, in this study it was observed greater proportions in the presence of Obstetric Nursing. The findings resemble recent studies (3,(20)(21) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the freedom of movement and position, in this study it was observed greater proportions in the presence of Obstetric Nursing. The findings resemble recent studies (3,(20)(21) .…”
Section: Discussionsupporting
confidence: 91%
“…This study demonstrated that the presence of Obstetric Nursing substantially reduces the rates of interventions performed and that, possibly, their presence is directly related to higher rates of vaginal deliveries. A recent study showed that the presence of Obstetric Nursing in LA care and delivery in maternity hospitals has a positive impact, including the reduction of cesarean sections (20) . The process of performing the delivery offered by Obstetric Nursing is centered on the promotion of practices based on scientific evidence seeking to rescue the protagonism of women in the process of giving birth (21) .…”
Section: Discussionmentioning
confidence: 99%
“…24 Essa fase transicional do campo obstétrico brasileiro confere um desafio adicional a ser enfrentado pelo ensino na modalidade de residência, considerando que 80% da carga horá-ria total do curso ocorre no serviço, sobretudo nos hospitais, e requer vigilância do corpo docente-assistencial para a formação de enfermeiras críticas, reflexivas e com atitudes políticas para superarem essas adversidades e atuarem como agentes de transformação desse modelo dominante.…”
Section: Eu Sou Enfermeira Do Centro Obstétrico E Somos Responsáveis unclassified
“…Esse modo de produzir o cuidado em saúde se opõem ao modelo médico dominante, centrado no trabalho instrumental, ou seja, em tecnologias duras 21 . Sob essa ótica, a utilização das tecnologias leves conferiu novos sentidos ao cuidado obstétrico prestado pelas discentes e produziu representações acerca do modelo assistencial desmedicalizado, o qual vem conferindo distinção e poder às enfermeiras obstétricas na atenção ao parto e nascimento, principalmente no município do Rio de Janeiro 7,18,20,22,23 .…”
Section: A Aprendizagem Apartir Dos Embates Com Os Médicosunclassified
“…Tais práticas obstétricas são comumente desenvolvidas por profissionais adeptos do modelo medicalizado, ainda que as recomendações oficiais e as evidências científicas as considerem como prejudiciais ou de uso criterioso 23 . Ainda, as atitudes impositivas das preceptoras evidenciam a posição dessas agentes em relação as residentes e o exercício de uma violência simbólica para legitimar suas concepções medicalizadas.…”
Section: Na Prática Eu Aprendi Episiotomia / Tinham Critérios Para unclassified